Comparing immunotherapies to other frequently used treatments of gastric cancer. Issue 10 (3rd October 2021) - Basile, Debora; Simionato, Francesca; Calvetti, Lorenzo; Cappetta, Alessandro; Pesavento, Annalisa; Mongillo, Marta; Roviello, Giandomenico; Rosati, Gerardo; Rossi, Gemma; Aprile, Giuseppe
ABSTRACT: Introduction : Although standard doublet chemotherapy represents the upfront gold standard to increase survival and improve quality of life of gastric cancer patients, overall improvements in long-term outcomes are modest and novel treatments are urgently needed. Among these, immunotherapy is an increasingly attractive option. Areas covered : A number of clinical trials have shown that checkpoint inhibitors may be of value, but many unclear issues remain controversial and should be promptly untangled. In our short review, we offer the current available data regarding immunotherapies in gastric cancers, discuss potential limits of the reported trials, compare outcomes of checkpoints inhibitor to those of standard chemotherapy or other novel treatments, and present basic principles of immune surveillance and immune escape that may be embraced in the near future with novel drug combinations. Expert opinion : Gastric cancer patients may benefit from immunotherapy, both given alone in advanced lines and upfront in combination with chemotherapy. We believe that appropriate patients' and tumor's selection are crucial issues to maximize its potential efficacy. In addition, we think that assay standardization, biomarker agreement, and translational studies will improve the benefit-to-risk ratio of these agents in the clinical practice.